2000
DOI: 10.1007/s002130000476
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of extinguished drug-taking behavior in rats: effect of the kappa-opioid receptor agonist, U69593

Abstract: The failure of U69593 to attenuate GBR 12909- or WIN 35,428-produced cocaine seeking suggests that the effect of this kappa-opioid receptor agonist on cocaine seeking is not mediated by interactions at the dopamine transporter. The ability of U69593 to attenuate RTI-55-produced cocaine seeking raises the possibility that kappa-opioids and cocaine may interact at common sites on the serotonin transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 40 publications
2
74
1
Order By: Relevance
“…A third possibility is that the increase in locomotor activity produced by DPMX interfered with the ability of the animal to perform the lever press operant. This interpretation is unlikely, however, since doses of caffeine (Worley et al 1994) and other drugs (Schenk and Partridge 1999;Schenk et al 2000) that produced reinstatement also increase locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third possibility is that the increase in locomotor activity produced by DPMX interfered with the ability of the animal to perform the lever press operant. This interpretation is unlikely, however, since doses of caffeine (Worley et al 1994) and other drugs (Schenk and Partridge 1999;Schenk et al 2000) that produced reinstatement also increase locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Experimenter-administered injections of indirect dopaminergic agonists such as cocaine, amphetamine, and methylphenidate (Schenk and Partridge 1999), as well as a number of direct dopaminergic D2-like receptor agonists including bromocriptine (Wise et al 1990), 7-OH-DPAT (Self et al 1996) and quinpirole (Self et al 1996;De Vries et al 1999) led to cocaine seeking. The dopamine transporter blocker GBR 12909 and the cocaine analogs WIN 35,428 and RTI-55 (Schenk et al 2000) also produced cocaine seeking. A dissociation between a role of dopamine D1-like and D2-like receptors has been suggested since D2-like, but not D1-like, agonists reinstated extinguished cocaine-taking behavior (Self et al 1996;DeVries et al 1999).…”
mentioning
confidence: 99%
“…Co-administration of kappa receptor agonists with cocaine has been shown to attenuate the rewarding and behavioral effects of cocaine. Pretreatment with kappa agonists has been shown to decrease self-administration of cocaine (Glick et al 1995;Mello and Negus 1998;Negus et al 1997;Schenk et al 1999), cocaine place preference (Crawford et al 1995;Schenk et al 1999), locomotor sensitization (Schenk et al 1999), and cocaine-induced reinstatement (Schenk et al 1999(Schenk et al , 2000. These findings have led to the hypothesis that cocaine self-administration could be attenuated by pretreatment with kappa agonists.…”
Section: Clinical Implications Of Kappa Antagonism On Drug Reinstatementmentioning
confidence: 99%
“…For example, previous studies in both nonhuman primates and rats have demonstrated that κ agonists functionally attenuate many of the behavioral effects of cocaine, including place preference [6][7][8] , self-administration [9][10][11][12] and the reinstatement of extinguished drug-taking behavior in an animal model of relapse [12,13] . However, these selective agonists produce many severe, undesirable side effects such as salivation, emesis, and sedation in nonhuman primates [10,11] , which may limit the clinical utility of κ agonists for the treatment of drug abuse.…”
Section: Introductionmentioning
confidence: 99%